2020
DOI: 10.5430/ijfr.v11n4p231
|View full text |Cite
|
Sign up to set email alerts
|

The Dynamics Between Dividends, Financing and Investments: Evidence From Jordanian Companies

Abstract: Dividend decisions, Financing decisions and Investment decisions are three very imperative decisions taken by a firm. The effect of these decisions is on the performance of the firm which subsequently effects the valuation of the firm. These decisions in a firm are also influenced by the growth and status of the respective economy.The current research attempts to analyze the dynamics between these three major decision areas and also assess their relationship with the market value of the firm. These dyn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…In this case, investment spending provides a positive signal about the company's growth so that it can increase firm value. This statement is supported by several studies which have found that investment decisions have an effect on firm value (Al Daas et al, 2020;Pramartha et al, 2020;Susanti et al, 2019). Thus, we propose this hypothesis [1]:…”
Section: Hypothesis Developmentmentioning
confidence: 61%
See 2 more Smart Citations
“…In this case, investment spending provides a positive signal about the company's growth so that it can increase firm value. This statement is supported by several studies which have found that investment decisions have an effect on firm value (Al Daas et al, 2020;Pramartha et al, 2020;Susanti et al, 2019). Thus, we propose this hypothesis [1]:…”
Section: Hypothesis Developmentmentioning
confidence: 61%
“…Information on the company's investment decisions is a signal that the company has good growth opportunities or prospects so that it is expected to increase share prices and the prosperity of shareholders. Several studies have proven that investment decisions are a positive signal in improving the company, such as in a study conducted by Al Daas et al (2020) which explains that one of the focuses of the driver of firm value in Jordan is related to investment decisions. This is also similar to the findings by Pramartha et al (2020) that investment decisions have a positive effect on firm value but with a different object, which is BUMN companies listed on the Indonesia Stock Exchange.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dividend, financing, and investment decisions are crucial corporate finance decisions which influence a firm's value (Daas et al 2020). The proponents of residual theory avow the dividend as a passive residual (Brav et al 2005;Higgins 1972).…”
Section: Financing and Investment Decisionsmentioning
confidence: 99%